Relationship Between Sedentary Behavior and Cognitive Function in Children in Phase C - Sita Adelia; Lukmannul Haqim Lubay; Wildan Alfia Nugroho; Gano Sumarno (Journal of Physical Education Health and Sport, 2025)
This study aimed to analyze the relationship between sedentary behavior and cognitive function in phase C elementary school students (aged 10–12 years). A quantitative approach with a correlational design was used in 291 students in Cibeunying Kidul District, Bandung City. Sedentary behavior was measured using the Adolescent Sedentary Activity Questionnaire (ASAQ), while cognitive function was measured using the Indonesian version of the Mini-Mental State Examination (MMSE). Data analysis was performed using Spearman’s rho correlation test. The results showed a significant but weak negative relationship between sedentary behavior and cognitive function (r = –0.121; p = 0.040). This finding indicates that the higher the level of sedentary behavior, the lower the child’s cognitive function score. Theoretically, these results support the view that physical activity plays an important role in maintaining and improving cognitive function, while sedentary behavior can hinder it. The practical implications of this study emphasize the importance of involving parents, teachers, and schools in reducing the duration of children’s sedentary activities through programs that increase enjoyable physical activity and are integrated with learning activities. This study contributes to local literature regarding the impact of sedentary behavior on the cognitive development of elementary school-aged children.